Managers' Time Orientation and Its Reflection in Organizational Culture: Tracing the Presence of The Construct of Time in The Leader-Organization Relationship - Joanna M. MICHALAK (Communications of International Proceedings, 2023)
Purpose: The purpose of this research is to establish the potential relation between temporal orientation of managers and culture of their organizations focusing on Schein's theory of organizational culture and time orientation construct developed by Zimbardo and Boyd.  Method: This review article focuses on how individual time perspective of organizational leaders through managerial behaviors is reflected in organizational culture. The review includes syntheses of the relevant literature relating to managerial behavior conditioned by the time factor and the influence of those behaviors on the components of organizational culture.  Findings: Recent research indicates that the way we perceive time has a profound effect on human behavior and its effects. This research shows that elements of organizational culture according to Schein are shaped by managerial behavior in different ways depending on the individual time orientation of managers. The author posits that looking at research in terms of time is a powerful tool in describing organizational phenomena, in particular organizational culture.
Keywords: Time Perspective; Temporal Orientation; Zimbardo Time Perspective Inventory; Organizational Culture; Leaders